A materials management study of Twin Oaks Food Corporation - Castillo, Althea F. (College of Engineering, 1995)
Twin Oaks Corporation is a manufacturer of consumer and specialty chocolates, and marshmallows.It has 150-square meter plant located in Cubao and a larger plant at Malolos, Bulacan. Nevertheless, the study concentrated only to the manufacture of consumer chocolates which are manufactured in Cubao. During the study, the group observed that there were some "inefficiencies" or problems in the plant. They are: (1) No official forecast used in manufacturing; (2) Molding machine has greater capacity then wrapping machine; and (3) Machine's rate of motion is too fast.Based on these main problems, symptoms were also identified i.e. overstacking of raw materials and packaging materials, disorganized materials handling and storing, decrease in productivity brought about by scrap and wastes, etc. Given this situation, the group was able to recommend several alternatives which would be of help to the company. They are: (1) To officially follow the forecasting technique used by the Marketing Department; (2) To have a new design of storage tray for chocolates; and (3) avoid reconditioning the machines on in-between shifts of workers. The explanations of these assertions are given in the Analysis and Recommendations part of the paper.